1, 2, 5, 6‐Naphthalene Diimides: A Class of Promising Building Blocks for Organic Semiconductors. Issue 10 (22nd March 2023) - Zhao, Zheng; Ge, Congwu; Zhao, Xueqian; Huang, Jintao; Gao, Xike
Comprehensive Summary: Organic semiconductors have drawn extensive attention due to their optoelectronic properties and wide applications in organic optoelectronics. In comparison with the popular 1, 4, 5, 8‐naphthalene diimides (1, 4, 5, 8‐NDIs), the angular‐shaped 1, 2, 5, 6‐NDIs have exhibited tunable photophysical properties, self‐assembly behaviors and charge transporting properties. Due to these unique features, 1, 2, 5, 6‐NDIs show great potential for construction of high performance π‐functional materials. In this review, we highlight the recent advances and future prospects of 1, 2, 5, 6‐NDI‐based π‐systems in the field of organic optoelectronics, including molecular design, synthesis, structure‐property relationships as well as the applications in high performance organic field‐effect transistors, organic photovoltaics, perovskite solar cells, and so on. What is the most favorite and original chemistry developed in your research group? Chemistry of π‐functional materials by using naphthalene and azulene as the basic structural units. How do you get into this specific field? Could you please share some experiences with our readers? This comes from my previous research experience, independent thinking and academic exchange & discussion. When I was a PhD student, my research topic focused on p‐type organic semiconductors. Since I independently carried out scientific research, my research interest turned to developing more challenging n‐type organic semiconductors by using core‐expanded 1, 4, 5, 8‐naphthalene diimides (NDIs). Later on, 1, 2, 5, 6‐NDIs as high‐performance organic semiconductors, the topic of this review paper, entered our study perspective based on the concept of isomerism. Also, based on the concept of isomerism and academic discussion, azulene, the isomer of naphthalene with unique chemical structure and physicochemical properties, became the dominant building block for constructing novel π‐functional materials in my group. How do you supervise your students? Select a research topic with scientific significance and certain challenges, let students consult and intensively read relevant literatures and obtain research inspiration, basic knowledge, experimental skills, writing skills, etc . Encourage students to think independently, try more, and pay more attention to communication and cooperation. Fully train students to write research papers independently. The last but not the least, advocate the academic spirit of being innovative, pursuing excellence as well as rigorous scholarship. What is the most important personality for scientific research? Curiosity and perseverance. What are your hobbies? Reading and walking. If you have anything else to tell our readers, please feel free to do so. No one can imprison your mind and hold your hand to prevent you from doing research work, follow your heart to do what you like and different from others. Abstract : Organic semiconductors are attracting more and more attention due to their novel optoelectronic properties and wide applications in organic optoelectronics. Exploration of new π‐conjugated building blocks plays a key role in the development of organic semiconductors. In comparison with the popular 1, 4, 5, 8‐naphthalene diimides (1, 4, 5, 8‐NDIs), the angular‐shaped 1, 2, 5, 6‐NDIs exhibited tunable photophysical properties, self‐assembly behaviors and charge transporting properties. Due to these unique features, 1, 2, 5, 6‐NDIs show great potential for construction of high performance π‐functional materials. In this review, we highlight the recent advances and future prospects of 1, 2, 5, 6‐NDI‐based π‐systems in the field of organic optoelectronics, including molecular design, synthesis, structure‐property relationships as well as the applications in high performance organic field‐effect transistors, organic photovoltaics, perovskite solar cells, and so on.